Tradisi Med-Medan di Banjar Kaja Desa Adat Sesetan Kota Denpasar Bali dalam Perspektif Filsafat Nilai Max Scheler - Gede Agus Siswadi; Septiana Dwiputri Maharani (Undiksha, 2022)
The culture or tradition in Bali is full of philosophical values, especially the Med-Medan tradition in Banjar Kaja, Sesetan Traditional Village, Denpasar City. However, due to the lack of literacy, people's knowledge and understanding of the tradition is only limited to euphoria. This article seeks to explore and analyze in depth the values contained in the Med-Medan tradition by using the perspective of Max Scheler's philosophy of values and using descriptive analytical methods. Based on the results of this study, it can be concluded that the philosophical values contained in the Med-Medan tradition are the value of enjoyment, vital or life values, psychological values and religious values. Based on the perspective of Max Scheler's hierarchy of values, religious values are priority values that residents want to achieve as a form of respect for their ancestors and devotion to God Almighty.